Balancing majority shareholder rights, minority shareholder rights and creditors rights in statutory mergers: in terms of the Companies Act 71 of 2008 - Ado, Jean Philippe Mathurin Sik (University of the Witwatersrand, Johannesburg, 2024)
Companies in their various forms are crucial to South Africa’s economy and its prosperity as they contribute towards wealth creation, social renewal and social welfare. In our growing world and borderless international markets, there are ongoing changes that affects a company’s competitiveness and productivity both nationally and internationally. These changes may be brought by the necessity to abide by international company law standards and practices that to some extent are aiming at sustainable economic growth and profitability. The South African company law regime, introduced since 1926, has undergone a series of amendments to ensure that its national companies and stakeholders benefit from the most updated legal system to galvanise its economy. In so doing, mergers and acquisitions represent one of the most cutting- edge concepts of company law around the world that encompasses the social, economic and financial needs of companies and that have been introduced in the current national company law regime. This research paper analyses the protections of shareholders and creditors in the statutory merger contained in the Companies Act 71 of 2008. It discusses also whether these protections are adequately balanced towards a fair consideration of majority shareholders, minority shareholders and creditors’ interests — which includes consideration of their rights too — in implementing a statutory merger. The main findings are that some protections are not properly balanced in consideration of the aforementioned parties’ interests. These include the appraisal remedy, the merger agreement and the oppression remedy — between minority and majority shareholders — and the creditors’ notification coupled with the court review, the open transferability of creditors’ contracts and the solvency and liquidity test — between majority shareholders and creditors — which in some aspects offers uncertainty in protecting their applicants. The approach adopted in the Canadian cases of Black & Decker and Loeb, set out in section 2 below, emphasises the importance of policy considerations which must meet the stated goals of s7 of the Companies Act 71 of 2008.
A research report submitted in fulfillment of the requirements for the Master of Laws, In the Faculty of Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Statutory merger; majority shareholders; minority shareholders; creditors; SDG-8: Decent work and economic growth